Major psychological and psycho-social conflicts and tasks in selected midlife Bildungsromans of Saul Bellow and Anne Tyler - Koloor, Keyhan Bahmani (2013)
The fact that the practices of defining a Bildungsroman as a novel narrating the formation of personality, or indiscriminately labelling novels with young or adult protagonists as Bildungsroman, are controversial and show the vagueness of this subgenre. Given that developmental psychology has shown that the quality of man‘s personality development is different at different stages of life—with the personality development of an adult literary character differing from that of a young character— there is a need to classify a subgenre of the Bildungsroman which deals with protagonists who are middle-aged. The first to recognise this need is Margaret Morganroth Gullette, who not only coined the term ―midlife Bildungsroman,‖ but also attempts to show that only authors who have undergone midlife transitions themselves can write such novels. However, Gullette‘s approach suffers from a number of drawbacks, primarily from her employment of an eclectic intertextual psycho-biographical meth d, in which intrinsic and extrinsic approaches are mixed together with psycho-biographical analyses of the authors‘ lives. This study will therefore explore the possibility of presenting a more complete theoretical framework to analyse the major psychological and psychosocial conflicts faced by the protagonists of four such midlife Bildungsromans, namely Saul Bellow‘s Seize the Day (1956) and Herzog (1964), as well as in Anne Tyler‘s Morgan‟s Passing (1980) and Back When We Were Grownups (2001). This framework will be based on two phenomena, individuation and midlife identity crisis. To discuss these concepts, a triangular theoretical approach, based on Jungian, Eriksonian and Levinsonian adult development theories will be used to show that midlife Bildungsromans are structured on a series of related psychological conflicts and tasks that allow for the classification of the subgenre as distinct from the conventional Bildungsroman. This study indicates and tests a pattern of adulthood individuation, consisting disintegration-midlife crisis-reintegration, as a fixed narrative pattern in midlife Bildungsromans.